Dual-Task Interference in a Simulated Driving Environment: Serial or Parallel Processing? - Abbas-Zadeh, Mojtaba; Hossein-Zadeh, Gholam-Ali; Vaziri-Pashkam, Maryam (Frontiers in Psychology, 2021)
When humans are required to perform two or more tasks concurrently, their performance declines as the tasks get closer together in time. Here, we investigated the mechanisms of this cognitive performance decline using a dual-task paradigm in a simulated driving environment and examined the serial/parallel nature of processing during dual-task performance. Participants performed a lane change task, along with an image discrimination task. We systematically varied the time difference between the onset of the two tasks (Stimulus Onset Asynchrony, SOA) and measured its effect on the amount of dual-task interference. Results showed that the reaction times (RTs) of two tasks in the dual-task condition were higher than those in the single-task condition. SOA influenced RTs of both tasks when they were presented second and the RTs of the image discrimination task when it was presented first. Manipulating the predictability of the order of the two tasks, we showed that unpredictability attenuated the effect of SOA by changing the order of the response to the two tasks. The drift diffusion modeling results indicated that performing two tasks concurrently affects both the rate of evidence accumulation and the delays outside the evidence accumulation period, suggesting that the two tasks are performed in a partial-parallel manner.